Síntese por moagem reativa de hidretos complexos multicomponentes à base de magnésio contendo vanádio: estudo exploratório de estrutura e propriedades de absorção/dessorção de hidrogênio - Matheus, Felipe Henrique (Universidade Federal de São Carlos, 2025)
Solid-state hydrogen storage via metal hydrides (MHs) is a promising alternative for its utilization as a sustainable energy carrier, with particular emphasis on Mg hydrides with transition metals (TM): Mg2(TM)Hx (TM = Fe, Ni or Co). However, multicomponent hydrides featuring multiple primary TMs remained largely unexplored. This thesis aimed at the synthesis and characterization of new Mg2(TM)Hx multicomponent hydrides using reactive milling with the incorporation of the TM vanadium. An initial synthesis attempt involving the elements Fe, Ni, Co, V, Cr, Mn, and Ti demonstrated the unprecedented formation of multicomponent hydrides when TM = Co, V, Fe, and Ni. Following this discovery, a systematic study was performed on the synthesis of MHs with compositions using these TMs and the characterization of phase transformations during desorption by in situ XRD using synchrotron radiation. Finally, the compositions Mg2(Fe1/3Ni1/3V1/3)Hx and Mg2(Fe1/3V1/3Co1/3)Hx were selected for an in-depth investigation of their storage properties. The results revealed good H2 absorption and desorption kinetics at 350°C. However, the hydride phase (of the Mg2FeH6 type) with multi-principal elements in the TM position proved to be poorly reversible during cycling. It was found that, after the first desorption, the transition metals segregate into cubic phases (BCC) that do not reconstitute the original multicomponent phase during absorption. Despite this irreversibility of the multicomponent phase, the resulting composite (the "milled mixture") maintained a stable cyclic storage capacity of CHmax ≈ 3.3 wt%, attributed mainly to the reversible reaction of the segregated Mg/MgH2, in addition to the fraction (< 25 wt%) of the Mg2(TM)H6 multicomponent phase that forms during H2 absorption.
Synthesis by reactive milling of multicomponent complex Mg-based hydrides containing vanadium: exploratory study of structure and hydrogen absorprion/desorption properties
Keywords: Absorção de hidrogênio; Ligas multicomponentes; Mg; Moagem de alta energia; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA; 7. Energia limpa e acessível; 9. Indústria, Inovação e Infraestrutura